Los principios del proceso contencioso administrativo a través de la jurisprudencia - Linares Paz Soldán, Melisa (Pontificia Universidad Católica del Perú, 2025)
General principles play a fundamental role in our legal system. From these principles, it is possible to deduce a series ofrules that allow for the construction of a coherent legal system inspired by common values. Under this perspective, principles also enable the interpretation of rules that are subsequently incorporated into the system, harmonizing their meaning and application according to their own guidelines. All of this results in jurisprudential decisions with greater argumentative solidity, coherence and predictability. Thus, in the procedural realm, principles provide a value-based background that must be compatible with the objectives of the process. The administrative litigation process is no exception, which is why it is necessary to delve deeper into the study of the principles recognized in the Law that Regulates the Administrative Litigation Process. Through this article, we will clarify the scope of the "specific" principles applicable to the administrative litigation process, highlighting the successes (and shortcomings) of their application in national jurisprudence.

Los principios generales cumplen una serie de funciones fundamentales en nuestro sistema jurídico. A partir de los principios, es posible deducir una serie de reglas que permitirán la construcción de un sistema jurídico coherente, inspirado en valores comunes. Bajo esa perspectiva, los principios también permiten interpretar las reglas que sucesivamente se incorporen al sistema, armonizando su sentido y aplicación bajo sus propias directrices. Todo ello repercute en pronunciamientos jurisprudenciales con mayor solidez argumentativa, coherencia y predictibilidad. Así, en el ámbito procesal, los principios otorgan un trasfondo valorativo que debe ser compatible con los fines del proceso. El proceso contencioso administrativo no es la excepción, de ahí que resulte necesario profundizar en el estudio de los principios reconocidos en la Ley que Regula el Proceso Contencioso Administrativo. A través de este artículo, precisaremos los alcances de los principios “específicos” aplicables al proceso contencioso administrativo, destacando los aciertos (y desaciertos) de su aplicación en la jurisprudencia nacional.
The principles of the contentious-administrative process through jurisprudence
Keywords: Administrative Procedural Law; Contentious Administrative Process; Principles; Integration; Procedural Equality; Favoring the Process; Ex Officio Substitution; Derecho procesal administrativo; Proceso Contencioso Administrativo; Principios; Integración; Igualdad Procesal; Favorecimiento del Proceso; Suplencia de Oficio; https://purl.org/pe-repo/ocde/ford#5.05.00